한의임상진료지침 기반 난임 처방-본초의 네트워크 클러스터 분석 - 이주영; Ju Young Lee; 이고운; Go Woon Lee; 최라윤; La Yoon Choi; 김미혜; Mi Hye Kim (大韓本草學會誌, 2025)
Objectives : This study aimed to select herbal prescriptions associated with pattern identifications for female infertility, as presented in the Korean Medicine Clinical Practice Guidelines (KM-CPGs) for infertility, and to conduct a network analysis based on these prescriptions. Through this analysis, we sought to identify frequently used prescriptions and the relationships among key medicinal herbs. Furthermore, we aimed to characterize core herbs and their combinations in the treatment of infertility, support the standardization of existing prescriptions, and suggest potentially effective new prescription combinations for clinical application. Methods : A network was constructed using data from 18 prescriptions associated with female infertility pattern identifications outlined in the KM-CPGs. Using Netminer 4, we performed centrality analysis to identify key prescriptions and herbs within the network and conducted clustering analysis to determine groups of herbs that are frequently used together. Results : Onbojongok -tang(溫飽種玉湯) exhibited high values across multiple centrality metrics, indicating its central role within the prescription network. Key herbs such as Angelicae Gigantis Radix (Danggui), Paeoniae Radix (Shaoyao), Glycyrrhizae Radix (Gancao), and Cnidii Rhizoma (Chuanxiong) also showed high centrality, suggesting their importance as core components in infertility treatment. Clustering analysis revealed three distinct herb groups characterized by kidney-tonifying and blood-nourishing effects, mind-stabilizing effects, and digestive-promoting effects. Conclusions : This study elucidates the structural relationships among prescriptions and herbs used in the treatment of female infertility. The findings support standardization of frequently used prescriptions and provide a basis for future clinical research and personalized herbal treatment strategies.